Engineering high-density microcrystalline boundary with V-doped RuO2 for high-performance oxygen evolution in acid - Han Wu; Zhanzhao Fu; Jiangwei Chang; Zhiang Hu; Jian Li; Siyang Wang; Jingkun Yu; Xue Yong; Geoffrey I. N. Waterhouse; Zhiyong Tang; Junbiao Chang; Siyu Lu (Nature Communications)
Abstract Designing efficient acidic oxygen evolution catalysts for proton exchange membrane water electrolyzers is challenging due to a trade-off between activity and stability. In this work, we construct high-density microcrystalline grain boundaries (GBs) with V-dopant in RuO2 matrix (GB-V-RuO2). Our theoretical and experimental results indicate this is a highly active and acid-resistant OER catalyst. Specifically, the GB-V-RuO2 requires low overpotentials of 159, 222, and 300 mV to reach 10, 100, and 1500 mA cm-2 geo in 0.5 M H2SO4, respectively. Operando EIS, ATR-SEIRAS FTIR and DEMS measurements reveal the importance of GBs in stabilizing lattice oxygen and thus inhibiting the lattice oxygen mediated OER pathway. As a result, the adsorbate evolution mechanism pathway becomes dominant, even at high current densities. Density functional theory analyses confirm that GBs can stabilize V dopant and that the synergy between them modulates the electronic structure of RuO2, thus optimizing the adsorption of OER intermediate species and enhancing electrocatalyst stability. Our work demonstrates a rational strategy for overcoming the traditional activity/stability dilemma, offering good prospects of developing high-performance acidic OER catalysts.